Напряженное состояние возле трещин на контуре отверстия в фотоупругой ортотропной пластине при ползучести - Войтович, Л.В.; Малежик, М.П.; Чернышенко, И.С. (Прикладная механика, 2010)
The stress-strain state is studied near the cracks locating on the contour of circular hole in a plate made of linearly elastic orthotropic composites under tension forces. The stress intensity coefficients (CIF) distribution near the crack tip is determined by the data of polarization-optical instrumentation. A dependence of CIF values on the ratio of crack length to hole radius as well as on mechanical properties of plate material is established.